Biosynthesis of the K99 surface antigen is repressed by alanine. - de Graaf, F K (1980)
The amino acid alanine induced a direct and specific repression of the biosynthesis of the K99 surface antigen in Escherichia coli strains harboring the K99 plasmid. In minimal medium with 0.5% glucose, 1 mM L-alanine was sufficient to reduce the K99 production by about 95%. The low production of the K99 antigen by strains growing on commercially available nutrient media seemed to be a result of the inhibitory effect alanine on the K99 biosynthesis.